Modeling sprawl of unauthorized development using geospatial technology : case study in Kuantan District, Malaysia - Hj. Mohd. Noor, Norzailawati; Mazlan, Hashim; Maged, Marghany (Taylor and Francis Group, 2010)
The paper explores a framework combining remote sensing and GIS-cellular automata concepts aimed at improving the modeling of unauthorized land use sprawl. Remote sensing data have been used in urban modeling and analysis, the use of high resolution remote sensing data in assessing unauthorized development is quite unexplored. This work has demonstrated systematic combination utilization of geospatial analyses tools to acquire new level of information to enable urban modeling and sprawl analysis in assisting urban sustainable management. In this study, Kuantan city, Malaysia was selected in simulation of the unauthorized land use with cellular automata concept for a period of 15 years (2000- 2015), with main input time-series land use observation from 1995 to 2005. The 2000 and 2005 land use input was also used as calibrated and test assessment of the simulation. The results show excellent agreement between in-situ changes of the un-authorized land use classes and the corresponding simulated classes within the same periods. In conclusion, cellular automata model can lead to new levels of understanding of how urban areas grow and change as in view of digital earth aspiration.